Anthrax toxin uptake by primary immune cells as determined with a lethal factor-beta-lactamase fusion protein. - Haijing Hu; Stephen H Leppla (PLoS ONE, 2009)
BACKGROUND:To initiate infection, Bacillus anthracis needs to overcome the host innate immune system. Anthrax toxin, a major virulence factor of B. anthracis, impairs both the innate and adaptive immune systems and is important in the establishment of anthrax infections. METHODOLOGY/PRINCIPAL FINDINGS:To measure the ability of anthrax toxin to target immune cells, studies were performed using a fusion of the anthrax toxin lethal factor (LF) N-terminal domain (LFn, aa 1-254) with beta-lactamase (LFnBLA). This protein reports on the ability of the anthrax toxin protective antigen (PA) to mediate LF delivery into cells. Primary immune cells prepared from mouse spleens were used in conjunction with flow cytometry to assess cleavage and resulting FRET disruption of a fluorescent beta-lactamase substrate, CCF2/AM. In spleen cell suspensions, the macrophages, dendritic cells, and B cells showed about 75% FRET disruption of CCF2/AM due to cleavage by the PA-delivered LFnBLA. LFnBLA delivery into CD4+ and CD8+ T cells was lower, with 40% FRET disruption. When the analyses were done on purified samples of individual cell types, similar results were obtained, with T cells again having lower LFnBLA delivery than macrophages, dendritic cells, and B cells. Relative expression levels of the toxin receptors CMG2 and TEM8 on these cells were determined by real-time PCR. Expression of CMG2 was about 1.5-fold higher in CD8+ cells than in CD4+ and B cells, and 2.5-fold higher than in macrophages. CONCLUSIONS/SIGNIFICANCE:Anthrax toxin entry and activity differs among immune cells. Macrophages, dendritic cells, and B cells displayed higher LFnBLA activity than CD4+ and CD8+ T cells in both spleen cell suspension and the purified samples of individual cell types. Expression of anthrax toxin receptor CMG2 is higher in CD4+ and CD8+ T cells, which is not correlated to the intracellular LFnBLA activity.